Challenges of Inclusive Tourism in Nepal: A Sociological Review - Shrestha, John (SMC Journal of Sociology, 2025)
This paper examines inclusive tourism practices and challenges among stakeholders in the Thamel area of Kathmandu and Gatlang in Rasuwa. Featuring 21 participants, including hotel and trekking company owners, guides, tourists, and community members, the research highlighted issues of accessibility, workforce diversity, and community participation. Key findings revealed limited accessibility for individuals with disabilities due to high costs and poor transportation in remote areas. Although there is some diversity among tourism entrepreneurs, employment opportunities for individuals with disabilities, especially the deaf, remain rare. Despite tourism generating income for local communities, external stakeholders often reap the benefits. Nepal has made progress with traveler-friendly policies, but challenges persist in infrastructure and awareness among operators, affecting services for travelers with special needs. Women and marginalized groups face participation barriers in the workforce, and local communities struggle to maintain cultural heritage amid modernization. Overall, the study concluded that inclusive tourism in Nepal is still developing, with significant improvements needed in policies, infrastructure, and stakeholder awareness to create a more inclusive environment.